2012
DOI: 10.1021/cm3014978
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation-Controlled Growth of Nanoparticles by Atomic Layer Deposition

Abstract: We demonstrate a method for growing metal nanoparticles (NPs) by atomic layer deposition (ALD) with the ability to vary aerial density and NP size using nucleation control. Self-assembled monolayers (SAMs) preadsorbed on the substrate serve as a template for subsequent growth of the NPs by ALD. Defects in the SAM resulting from incomplete formation time in solution are shown to act as nucleation sites for Pt. The strategy is demonstrated experimentally using ALD of Pt from a metal organic Pt precursor and O 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 63 publications
(74 reference statements)
3
69
0
Order By: Relevance
“…32 According to the isothermal model based on nucleation incubation, the surface coverage of deposited Pt can be calculated as follows:…”
Section: Resultsmentioning
confidence: 99%
“…32 According to the isothermal model based on nucleation incubation, the surface coverage of deposited Pt can be calculated as follows:…”
Section: Resultsmentioning
confidence: 99%
“…That is nucleation delay during the initial ALD cycles of noble metals occurs and has been reported to be due to the lack of adsorption sites [39,40] and/or large differences in the surface energy between substrate and noble metal [41,42]. Additional EDX data shown in Fig.…”
Section: Resultsmentioning
confidence: 79%
“…71,72 Earlier work from our group by Brennan et al 73 showed that ALD led to deposition of different sizes of quantum dots by limiting the growth to within the ALD nucleation regime. However, under some conditions it can also be used to grow nanoparticles, including QDs.…”
Section: Qd Sensitizers In Qdsscsmentioning
confidence: 99%
“…71,72 Earlier work from our group by Brennan et al 73 showed that ALD led to deposition of different sizes of quantum dots by limiting the growth to within the ALD nucleation regime. 71 In the same work, 73 Brennan et al reported solid-state PV devices on mesostructured TiO 2 sensitized by ALD-grown CdS QDs. The growth rate of CdS showed two significantly different regimes as illustrated in Fig.…”
Section: Qd Sensitizers In Qdsscsmentioning
confidence: 99%